Inonotus obliquus polysaccharide are linear molecules that alter the abundance and composition of intestinal microbiota in Sprague Dawley rats - Liu, Songqing; Zhou, Wenjing; Deng, Xin; Jiang, Wei; Wang, Yanping; Zhan, Jiasui; Hu, Binhong (Frontiers in Nutrition, 2023)
Introduction The macromolecular polysaccharide Inonotus obliquus polysaccharide (IOP) is composed of various monosaccharides, and it could modulate the composition and diversity of intestinal flora. However, its impact on the intestinal flora in rats of different genders remains unclear. Therefore, this study aims to investigate the structural changes of IOP and its effects on the intestinal flora after administration in male and female rats. Methods In this study, the molecular weight and purity of IOP were analyzed by high-performance gel permeation chromatography (HPGPC) and phenol sulfuric acid method, and NMR was used to confirm the chemical structure of IOP. Sex hormone [testosterone (T) and estradiol (E2)] levels and intestinal microbial changes were detected by enzyme-linked immunosorbent assay (ELISA) and 16S rRNA, respectively, after gavage of IOP (100 mg/kg) in male and female Sprague Dawley (SD) rats. Results HPGPC analysis showed that the average molecular weight (Mw) of IOP was 4,828 Da, and the total sugar content of the purified IOP was 96.2%, indicating that the polysaccharide is of high purity. NMR revealed that IOP is a linear macromolecule with an α-D-type glucose backbone. The results of ELISA and 16S rRNA showed that the IOP increased the abundance of beneficial bacteria, such as Clostridia_UCG-014 and Prevotellaceae_NK3B31, and reduced that of harmful bacteria, such as Colidextribacter and Desulfobacterota in the intestine of both male and female rats, and IOP changed the levels of sex hormones in male and female rats. Further analyses revealed that the increase in alpha diversity was higher in male than female rats. α diversity and β diversity revealed a significant difference in the composition of cecal microbiota between male and female rats in the control group, but IOP intake reduced this difference. Meanwhile, α analysis revealed a change in the composition of bacterial flora was more stable in male than female rats. Conclusions This study enhances our comprehension of the IOP structure and elucidates the alterations in intestinal flora following IOP administration in rats of varying genders. Nonetheless, further investigation is warranted to explore the specific underlying reasons for these discrepancies.